MOTIVASI KERJA PEGAWAI DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA KOTA BUKITTINGGI - Ilham , (Jurnal Bahana Manajemen Pendidikan, 2014)
The goal of this research are to see information about employee motivation. The population is 104 employee and the sample is 58 people that taken by stratified random sampling. The instrument of this research is question with Likert scale models that had tested for validity and realibility. Data analyzed using mean score and performance level. The results of this research are the Department of Education Employee Work Motivation to stay in pretty good category. Key word : Employee Motivation